Resveratrol increases AdipoR1 and AdipoR2 expression in type 2 diabetic nephropathy. Issue 1 (December 2016) - Park, Hoon; Lim, Ji; Kim, Min; Kim, Yaeni; Hong, You; Choi, Sun; Chung, Sungjin; Kim, Hyung; Choi, Bum; Kim, Yong; Chang, Yoon; Park, Cheol
Abstract Background Adiponectin has multiple functions including insulin sensitization, anti-inflammation and antiatherogenesis in various organs. Adiponectin activates 5′-adenosine monophosphate-activated protein kinase (AMPK) and peroxisome proliferator-activated receptor (PPAR)α via the adiponectin receptor (AdipoR) 1 and 2, which are critical for regulating lipids and glucose homeostasis and for controlling oxidative stress. We investigated whether resveratrol can inhibit renal damage in type 2 diabeticdb/db mice and the underlying mechanisms of its effects. Methods Four groups of male C57 BLKS/Jdb/m anddb/db mice and human glomerular endothelial cells (HGECs) were used. Resveratrol was administered to diabetic and nondiabetic mice by oral gavage for 12 weeks starting at 8 weeks of age. Results Indb/db mice, resveratrol increased serum adiponectin levels and decreased albuminuria, glomerular matrix expansion, inflammation and apoptosis in the glomerulus. Resveratrol increased the phosphorylation of AMPK and silent information regulator T1 (SIRT1), and decreased phosphorylation of downstream effectors class O forkhead box (FoxO)1 and FoxO3a via increasing AdipoR1 and AdipoR2 in the renal cortex. Furthermore, resveratrol increased expression of PPARγ coactivator (PGC)-1α, estrogen-related receptor-1α, and phosphorylated acetyl-CoA carboxylase and decreased sterol regulatory element-binding protein 1. This effect lowered the content of nonesterified fatty acid and triacylglycerol in the kidneys, decreasing apoptosis, oxidative stress and activating endothelial nitric oxide synthase. Resveratrol prevented cultured HGECs from undergoing high-glucose-induced oxidative stress and apoptosis by activating the AMPK–SIRT1–PGC–1α axis and PPARα through increases in AdipoR1 and AdipoR2 expression. Conclusions These results suggest that resveratrol prevents diabetic nephropathy by ameliorating lipotoxicity, oxidative stress, apoptosis and endothelial dysfunction via increasing AdipoR1 and AdipoR2 expression.